Digitalisasi Pembelajaran di Sekolah - Nasrullah Nasrullah; Ali Wira Rahman (Departement of Mathematics Education, 2023)
Education from time to time continues to experience changes, because if there is no change then the quality of education will be questioned while the current demands of the times are increasing. This causes education as one of the pillars that must remain firmly standing in the face of every challenge that exists, dismissing all changes whose direction can make the bad nation's generation forget its existence as a change being. Education must come with different and more challenging concepts, faces, methods, and materials to increase students' thinking stimuli. In addition, education must be able to give joy, not sadness. The combination of media and IT in school learning is a scourge and at the same time an opportunity for educators. Becoming afraid on the part of some educators because of their weak mastery of IT so they seem to be strangers in the learning process. But it becomes an opportunity for people or educators who can integrate with IT. The presence of the system provides a new spirit in dealing with the new normal situation so that there are no more students who cannot study well because learning must continue with various consequences. Research focuses on digitizing learning and teaching materials so that students can more easily access the material. This research is an ADDIE Research and Development model which produces a prototype of a learning website that can and is easily accessed by teachers and students. When all stages in making this website are completed, the researcher will fully hand it over to the school to be managed and even developed. This research produces 5 F learning, Creative, Innovative, Solution, Interactive and productive which makes students and teachers feel happy and easy in carrying out the learning process and developing teaching materials.